Determination of air-tightness of the packagings of electronic devices by the thermoacoustic method - Maliński, M. (Archives of Acoustics, 2005)
The method of determination of air-tightness of packagings based on the measurement of the thermoacoustic signals generated by transistor chips is described in this paper. This method makes possible the estimation of the radius of the hole in the packaging and, as a result, its air-tightness. In this paper the fitting of the theoretical model to experimental results is presented and discussed. Because of its simplicity and nondestructive character, the presented method can be applied in the quality control departments of the electronic industry.